Die Tagesschau-App und die Notwendigkeit der Schaffung eines ""Intermedienkollisionsrechts"" - Vesting, Thomas (Karlsruher Dialog zum Informationsrecht / Zentrum für Angewandte Rechtswissenschaft (ZAR), Karlsruher Institut für Technologie (KIT), 2013)
The article takes up the example of online news-services to describe the overall purpose of Germany's public broadcasting corporation within the new networks of electronic media. It argues that the rise of the Internet is an evolutionary jump in the history of media. For this reason the traditional constitutional regime of guaranteeing pluralism in broadcasting can no longer be applied as a rationale and justification. Rather, a new constitutional type of conflict of law rules should be inaugurated to cope with the rising economic competition between public and private online news-services.